Associate Prof. Dr Arun Gupta created beauty and cosmetic products from chicken feather keratin - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) researcher, Associate Professor Dr. Arun Gupta from Faculty of Chemical & Natural Resources Engineering (FKKSA) led a group of researchers to commercially produce beauty care products called Keraglow, made from keratin extracted from chicken feathers. The products included anti-aging cream, moisturiser, serum, shampoo and other hair care items.